2021
DOI: 10.1002/jia2.25833
|View full text |Cite
|
Sign up to set email alerts
|

HIV‐1 drug resistance among individuals who seroconverted in the ASPIRE dapivirine ring trial

Abstract: IntroductionA potential concern with the use of dapivirine (DPV) for HIV prevention is the selection of a drug‐resistant virus that could spread and reduce the effectiveness of non‐nucleoside reverse transcriptase (NNRTI)‐based first‐line antiretroviral therapy. We evaluated HIV‐1 seroconversions in MTN‐020/ASPIRE for selection of drug resistance and evaluated the genetic basis for observed reductions in susceptibility to DPV.MethodsMTN‐020/ASPIRE was a placebo‐controlled, Phase III safety and effectiveness st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…We undertook a comprehensive assessment of the 38 seroconversions in the HOPE open-label study of DPV ring and found infrequent NNRTI resistance. However, the overall rate of resistance observed among participants becoming HIV seropositive (20%) was higher than that observed in the DPV ring arm of the Phase III ASPIRE trial (10.4%), 12,24 but 20% is consistent with the contemporaneous national NNRTI pretreatment drug resistance rates of 10%–30% in Uganda, South Africa, and Zimbabwe as reported in the 2019 World Health Organization HIV Drug Resistance Report. 27 That the frequency of NNRTI resistance in HOPE participants who became HIV seropositive is similar to that of circulating NNRTI resistance in the community argues for transmitted drug resistance in HOPE participants and against selection of resistance by DPV.…”
Section: Discussionsupporting
confidence: 63%
“…We undertook a comprehensive assessment of the 38 seroconversions in the HOPE open-label study of DPV ring and found infrequent NNRTI resistance. However, the overall rate of resistance observed among participants becoming HIV seropositive (20%) was higher than that observed in the DPV ring arm of the Phase III ASPIRE trial (10.4%), 12,24 but 20% is consistent with the contemporaneous national NNRTI pretreatment drug resistance rates of 10%–30% in Uganda, South Africa, and Zimbabwe as reported in the 2019 World Health Organization HIV Drug Resistance Report. 27 That the frequency of NNRTI resistance in HOPE participants who became HIV seropositive is similar to that of circulating NNRTI resistance in the community argues for transmitted drug resistance in HOPE participants and against selection of resistance by DPV.…”
Section: Discussionsupporting
confidence: 63%
“…An exhaustive phenotypic evaluation of plasma-derived bulk-cloned HIV-1 with E138A and systematic reversion to 138E (wild-type) showed a modest reduction in susceptibility to DPV (median 4.7-fold) in some genotypic backgrounds but not others. Alterations in DPV susceptibility of viruses with E138A were independent of the study arm in ASPIRE [75 ▪▪ ].…”
Section: Resistance With the Dapivirine Ringmentioning
confidence: 88%
“…In the two Phase III DPV ring studies, a high but equivalent rate of NNRTI resistance was observed among seroconversions from both the active and placebo ring arms, indicating that resistance was likely transmitted and not selected by DPV ring use. In ASPIRE, 8 of 71 (11.3%) and 10 of 97 (10.3%) participants who seroconverted had one or more NNRTI mutations detected by Sanger sequencing [75 ▪▪ ]. Similarly, 13 of 82 (15.9%) in the DVR arm had NNRTI resistance compared to 8 of 57 (14.0%) in the placebo arm from the Phase III Ring study [76].…”
Section: Resistance With the Dapivirine Ringmentioning
confidence: 99%
“…As new PrEP drugs and delivery methods, such as the monthly dapivirine vaginal ring and the cabotegravir long-acting injectable, become available on the global market and as countries transition to alternative first-line ART regimens in the same drug classes as PrEP agents, more research and surveillance will be needed to monitor and limit the risk of HIVDR. 46,47 Systems developed to monitor for HIVDR with PrEP use must be adaptable to these new PrEP agents as drug resistance risk and profiles may change.…”
Section: Discussionmentioning
confidence: 99%